“El desarrollo emocional en los niños y niñas del subnivel inicial 2 de la unidad educativa Provincia de Cotopaxi” - Marquez Intriago, Kelly Alexandra (2023)
Nowadays, emotional development is the main axis for the development and control of emotions in each individual, beginning in the first years of a child's life. For that reason, the objective of this research is to "diagnose the emotional development in children from three to four years old in the initial sub-level 2 of the Cotopaxi Province Educational Unit of the Pujili canton. Firstly, the qualitative approach was used in descriptive, documentary, and field research. The research techniques used were the observation of 17 students and the interview of a teacher. Information was collected with the instruments' observation form and question guide. The results identify two dimensions: emotions and coexistence. The rating scale used in the results is "beginning, in process, and achieved. Furthermore, in the dimension of emotions, 14 children are at the beginning of the development of emotions, and 3 children are in the process of acquisition. In the dimension of coexistence, 15 children are at the beginning, and 2 children are in the process. To sum up, it is concluded that there is an educational need to strengthen emotional development in children in the first sublevel.